2019
DOI: 10.1016/j.cbpb.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-protein interactions in mitochondrial membranes from bivalve mollusks: molecular strategies in different species

Abstract: The mitochondrial FF-ATPase, the key enzyme in cell bioenergetics, apparently works in the same way in mollusks and in mammals. We previously pointed out a raft-like arrangement in mussel gill mitochondrial membranes, which apparently distinguishes bivalve mollusks from mammals. To explore the relationship between the microenvironmental features and the enzyme activity, the physico-chemical features of mitochondrial membranes and the FF-ATPase activity temperature-dependence are here explored in the Manila cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…This is also confirmed by the calculated generalized polarization functions, where a low ExGP and the presence of a negative slope as the wavelength increases are indicative of a fluid phase ( Fig. 2E,F) [46,47]. Upon addition of cholesterol, there is an increase in the overall ExGP function in all cases, indicating an ordering of the bilayer.…”
Section: Preparation and Characterization Of Sma Nanodiscssupporting
confidence: 73%
“…This is also confirmed by the calculated generalized polarization functions, where a low ExGP and the presence of a negative slope as the wavelength increases are indicative of a fluid phase ( Fig. 2E,F) [46,47]. Upon addition of cholesterol, there is an increase in the overall ExGP function in all cases, indicating an ordering of the bilayer.…”
Section: Preparation and Characterization Of Sma Nanodiscssupporting
confidence: 73%
“…PUFA is also prevalent in aqueous metazoans to maintain membrane fluidity 88 . Accordingly, investigating evolution of lipid unsaturation in non-mitochondrial membranes and correlated sequence divergence in membrane-embedded proteins would be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway and the Toll-like receptor signaling pathway are important in the immune response of mollusks [32][33][34][35]. Cholesterol metabolism can significantly affect the growth and development of mollusks [36,37]. The GO and KEGG enrichment analyses revealed that low-salinity seawater has the potential to affect the growth and development of S. esculenta larvae.…”
Section: Enrichment Analysis Of Degsmentioning
confidence: 99%